2011
DOI: 10.1007/s10008-011-1467-8
|View full text |Cite
|
Sign up to set email alerts
|

Nano-sized La0.8Sr0.2MnO3 as oxygen reduction catalyst in nonaqueous Li/O2 batteries

Abstract: Nano-sized La 0.8 Sr 0.2 MnO 3 prepared by the polyethylene glycol assisting sol-gel method was applied as oxygen reduction catalyst in nonaqueous Li/O 2 batteries. The as-synthesized La 0.8 Sr 0.2 MnO 3 was characterized by X-ray diffraction (XRD), scanning electron microscopy, and Brunauer-Emmet-Teller measurements. The XRD results indicate that the sample possesses a pure perovskite-type crystal structure, even sintered at a temperature as low as 600°C, whereas for solid-state reaction method it can only be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…To a certain degree, all of these researches have evidenced the promising application of NiCo 2 O 4 as efficient electrocatalyst in Li-O 2 battery. Simultaneously, these researches also highlights the importance of favorable cathode structure and intrinsically high catalytic activity of cathode material, which is further supported by Zhu et al [123] In detail, they reported a new electrode structure constituted of vertically aligned carbon nanosheets and metal hydroxide (M(OH) x @CNS) hybrid arrays, integrating [126][127][128][129][130][131] However, in many cases, perovskite catalysts obtained by conventional synthesis methods have quite low intrinsic electronic conductivities and small specific surface areas, which lead to low catalytic activity, thus limiting their usage. Therefore, to improve the performance of the perovskite materials in Li-O 2 batteries, a variety of modification methods were employed, including (a) combination of ABO 3 with conductive nanocarbons such as carbon black, carbon nanotube, and graphene to enlarge the effective contact area for catalysis and improve the electrical conductivity of the perovskite oxide/carbon electrodes; (b) synthesis of porous-structured perovskites with increased number of oxygen pathways and specific surface area to enhance the catalytic performance.…”
Section: Noble Metal Metal Oxides and Other Electrocatalystsmentioning
confidence: 68%
“…To a certain degree, all of these researches have evidenced the promising application of NiCo 2 O 4 as efficient electrocatalyst in Li-O 2 battery. Simultaneously, these researches also highlights the importance of favorable cathode structure and intrinsically high catalytic activity of cathode material, which is further supported by Zhu et al [123] In detail, they reported a new electrode structure constituted of vertically aligned carbon nanosheets and metal hydroxide (M(OH) x @CNS) hybrid arrays, integrating [126][127][128][129][130][131] However, in many cases, perovskite catalysts obtained by conventional synthesis methods have quite low intrinsic electronic conductivities and small specific surface areas, which lead to low catalytic activity, thus limiting their usage. Therefore, to improve the performance of the perovskite materials in Li-O 2 batteries, a variety of modification methods were employed, including (a) combination of ABO 3 with conductive nanocarbons such as carbon black, carbon nanotube, and graphene to enlarge the effective contact area for catalysis and improve the electrical conductivity of the perovskite oxide/carbon electrodes; (b) synthesis of porous-structured perovskites with increased number of oxygen pathways and specific surface area to enhance the catalytic performance.…”
Section: Noble Metal Metal Oxides and Other Electrocatalystsmentioning
confidence: 68%
“…As one of the most frequentlyeused cathode materials in solid oxide fuel cells, La 0.8 Sr 0.2 MnO 3 (LSM) perovskite oxide has demonstrated promising catalytic properties in lithiumeair batteries with noneaqueous electrolyte [17,26]. For example, Xu et al have proposed porous La 0.75 Sr 0.25 MnO 3 nanotubes by electrospinning as electrocatalyst for lithiumeO 2 battery, which demonstrated ultrahigh charge and discharge capacities [17].…”
Section: Introductionmentioning
confidence: 98%
“…In order to commercialize the lithium-air battery, however, there are many problems to be technically solved [6,7]. Particularly, since lithium peroxide (Li 2 O 2 ) produced at the cathode during 25 discharge process is in solid phase, it could blocks the pores on the porous carbon electrode surface and reduce the contact area of oxygen and electrolyte, resulting in the degradation of lithium-air battery performance [8,9]. Since the Li 2 O 2 acts as an insulator, moreover, the electron transfer is also not easy and high 30 overpotential will be required to decompose Li 2 O 2 and Li 2 O into O 2 and Li on recharging.…”
Section: Introductionmentioning
confidence: 99%